Analyzing the Communication Strategy of the Youth Information and Counseling Center in Implementing the Marriage Age Maturity Program - Agustina, Muthia; Kusumaningtias, Intan Tri; Amaliasari, Diana (Journal of Social Studies Arts and Humanities (JSSAH), 2024)
This study aims to analyze the strategic communication implemented by the Youth Information and Counseling Center (Pusat Informasi dan Konseling Remaja or PIK-R) Bunga Harapan in promoting the Marriage Age Maturity (Pendewasaan Usia Perkawinan or PUP) program among adolescents in East Bogor. The PUP program seeks to increase youth awareness of the physical, mental, and social readiness required before entering marriage, aligning with Indonesia’s national efforts to prevent early marriage. This research uses a qualitative descriptive method, focusing on the communication strategy framework of Lasswell—who says, what message, in which channel, to whom, and with what effect. Data were collected through in-depth interviews, observation, and documentation from PIK-R coordinators, peer educators, and target adolescents. The findings show that PIK-R Bunga Harapan effectively applies interpersonal communication and social media campaigns as the primary channels for delivering PUP messages. Message design emphasizes emotional and rational appeals, using relatable language and local cultural values to encourage behavioral awareness. However, limited funding, uneven information access, and inconsistent participation remain significant obstacles. The study concludes that well-planned strategic communication, supported by youth participation and institutional collaboration, is crucial in strengthening the effectiveness of the Marriage Age Maturity program and reducing early marriage rates among adolescents.